What determines pumping behaviour of tubewell owners: marginal cost or opportunity cost? - Kishore, Avinash; Verma, S. (International Water Management Institute, 2003)
Research highlight based on a paper titled ?Pumping behaviour under different tariff regimes: The Anand survey?